PELINDUNGAN HUKUM TERHADAP INVENTOR PEMEGANG HAK PATEN TNI ANGKATAN DARAT DALAM PENDAFTARAN HAK PATEN DI INDONESIA - Benedicta Angela Prasetyo; Christine S.T. Kansil (Jurnal Hukum Adigama, 2021)
The technological development of a country cannot be separated from the guarantee of intellectual property protection that applies to that country. Intellectual Property Rights or abbreviated HKI are equivalent to Intellectual Property Rights is a right arising from the thinking of the human brain which produces a product or process that is beneficial to humans. Patents are part of Intellectual Property Rights, which in this framework are included in the category of industrial property rights. This study aims to look at legal protection for inventors who produce inventions in the field of military technology. This type of research used in this research is normative legal research supported by interview data with experts. In this case, a military invention does not have a patent certificate because it has not registered it in a patent right, therefore there is no protection against this military invention. Until now, all of the technology in the Army cannot be patented, because there are no rules as to how to apply for such patents. In this case Peraturan Panglima and Peraturan Kepala Staf Angkatan Darat have not been regulated even though Article 109 of Law No. 13 of 2016 concerning Patents and Article 2, Article 3, and Article 4 of Presidential Regulation No. 77 of 2020 concerning the Procedure for the Application of Patents by the Government, a statement that, specifically for the military, which is managed by the Government, the government cannot conduct such Patents alone, the government will appoint a third party.